A study of biochemical changes in river buffaloes (Bubalus bubalis) naturally infected with Anaplasma marginale - Jalali, SM; Nikvand, AA; Gharibi, D; Razi Jalali, M; Yazdkhasti, M; Kaviani, F (Journal of the Hellenic Veterinary Medical Society, 2023)
Anaplasma marginale as an intracellular rickettsia, endemic in tropical and subtropical regions of the world. This study was performed to determine A. marginale infection, molecularly, and to investigate its effects on some serum biochemical parameters in river buffaloes referred to Ahvaz abattoir, Southwest Iran. A total of 103 apparently healthy river buffaloes were randomly sampled. Whole blood samples were subjected to PCR analysis and blood smears were examined microscopically for the presence of Anaplasma inclusions. Serum biochemical parameters including total protein, albumin, glucose, urea, iron, total bilirubin, total cholesterol, Calcium, Phosphorus and Magnesium concentrations, aspartate aminotransferase (AST) and alkaline phosphatase (ALP) activities and also serum electrolytes comprising Na and K were assessed. The results revealed that 16 and 32 samples were infected with A. marginale in microscopic and PCR assessment, respectively. Serum biochemical analysis showed no significant difference between A. marginale infected and non-infected buffalo groups. It can be concluded that infection with A. marginale does not lead to much pathogenicity in river buffaloes, so that in infected animals, no clinical signs or abnormalities in the performance indicators of various organs can be detected at the laboratory level. However, the role of this species as a reservoir of this microorganism in nature and in the epidemiology and transmission of anaplasmosis to other species remains significant. Buffaloes can be a substitute to raising cattle in regions with high occurrence of anaplasmosis.